EFFECT OF FEEDING MARKET VEGETABLE WASTE ON WEIGHT GIAN OF RABBITS (Oryctolagus cuniculus L.) - Michael Stiff Kotambunan; Suddin Simanjuntak; Verawati Ida Yani Roring (Indonesian Biodiversity Journal, 2022)
Rabbits are livestock that has the potential to provide meat in a relatively short time, so people's consumption of animal protein is expected to be fulfilled. Market vegetable waste can also be used as feed, especially for rabbits. When processed into rabbit feed, waste is not only a product, but from the feed consumed by rabbits, it can produce meat of good quality. This study aimed to determine whether feeding vegetable waste can increase rabbit body weight and whether combining pellets and vegetable waste can increase rabbit body weight. This study used a quantitative experimental method using an experimental design that was Completely Randomized Design (CRD) with six treatments and four replications. The survey results showed that feeding vegetable waste was effective as feed for rabbits because it could increase the body weight of rabbits (Oryctolagus Cuniculus L.). The more balanced the market vegetable waste feed in the form of cabbage, carrots, pattern (young corn shoots) and pellets were given, the higher the weight gain of rabbits (Oryctolagus Cuniculus L.). Market vegetable waste is not recommended as a good feed. Still, it can be used as a supplement only because research results show that market vegetable waste does not have a significant effect.